Hydrogen-enhanced densified twinning (HEDT) in a twinning-induced plasticity (TWIP) steel. (1st January 2021) - Zhang, Cheng; Zhi, Huihui; Antonov, Stoichko; Chen, Lin; Su, Yanjing
Abstract: The effect of hydrogen on the twinning evolution in a twinning-induced plasticity (TWIP) austenitic steel was investigated at different strain levels. The presence of hydrogen decreased the twin thickness and increased the twin density in individual twin bundles, in comparison with the hydrogen-free condition. This mechanism, reported for the first time, was termed hydrogen-enhanced densified twinning (HEDT). Based on these experimental observations, the effect of hydrogen on twinning was analyzed from the three stages of nucleation, growth and stability. HEDT may elevate the local stress, and thus significantly affect the hydrogen embrittlement (HE) of TWIP steels. Graphica abstract: Image, graphical abstract